Meningkatkan Hasil Belajar Matematika Materi Akar Pangkat Tiga dengan Metode Drill - Angela Samosir; Nurmalina Nurmalina; Molli Wahyuni (Departement of Mathematics Education, 2022)
This study examines the learning and learning outcomes of students' mathematics. The problem that is often encountered in learning mathematics is the low learning outcomes of students who have not reached the school's KKM. This study aims to determine the increase in results and learning activities of class VI students of SD Negeri 013 Rambah on cube root material using the drill method. This research is a classroom action research carried out in two cycles consisting of four stages, namely planning, implementation, perception, reflection. Reflection is used as a basis for planning improvements in the next cycle. The research data was obtained through observation sheets and the results of learning tests in cycle I and cycle II. obtained into data to be analyzed descriptively. The results of this study indicate that the use of the drill method can improve student learning outcomes and activities. Increasing student activity from the less category in cycle I to the good category in cycle II. The learning outcomes of students' KKM mastery in cycle I were only 16 students (50%), in cycle II it increased to 29 students (91%). Based on the findings of the researchers, it can be concluded that learning mathematics about cube roots using the drill method can improve the results and learning activities of class VI students at SD Negeri 013 Rambah.